Spatiotemporal dynamics of nicotinic acetylcholine receptors and lipid platforms - Barrantes, Francisco José (2017)
Fil: Barrantes, Francisco J. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Neurobiología Molecular; Argentina